Hijacking PrPc-dependent signal transduction: when prions impair Aβ clearance - Hernandez-Rapp, Julia; Martin-Lannerée, Séverine; Hirsch, Théo Z.; Launay, Jean-Marie; Mouillet-Richard, Sophie (Frontiers in Aging Neuroscience, 2014)
The cellular prion protein PrPc is the normal counterpart of the scrapie prion protein PrP Sc, the main component of the infectious agent of transmissible spongiform encephalopathies. The recent discovery that PrP c can serve as a receptor for the amyloid beta (Aβ) peptide and relay its neurotoxicity is sparking renewed interest on this protein and its involvement in signal transduction processes. Disease-associated PrP Sc shares with Aβ the ability to hijack PrP c-dependent signaling cascades, and thereby instigate pathogenic events. Among these is an impairment of Aβ clearance, uncovered in prion-infected neuronal cells. These findings add another facet to the intricate interplay between PrP c and Aβ. Here, we summarize the connection between PrP-mediated signaling and Aβ clearance and discuss its pathological implications.